ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN KINERJA PETUGAS TUBERKULOSIS (TB) PUSKESMAS DI KABUPATEN JEMBER - Sutrisno Sutrisno (Jurnal Ilmu Kesehatan Masyarakat, 2011)
The realization of Case Detection Rate (CDR) per primary health center was still below the target, namely 55 % of the total 49 Primary Health Center. Although there was a positif trend of increase of realization of the CDR target, however the increase was relatively slow, only 2 % per annum. The realization of CDR in Primary Health Center was very much affected by; first, the active participation of the community (passive case detection); second, the participation of private health services nearby the primary health centers; third, the human resource available at the Primary Health Centers (Performance of the TB officer. The objective of this research was to analyze the factors ( age, knowledge, motivation, incentives), which were dominantly assosiated to performance of the TB officers at the Primary Health Centers in Jember District in 2010. The  research used an observational analytical method with cross sectional appoach. The population of the study was all the TB officers  at the primary health centers in Jember District. The total samples were 49 persons (total population). The data were collected by using questionnaires and structure interviews. The methods of data analysis were univariate and bivariate. The results of bivariate analysis based on the value of prevalence ratio for each variable were : knowledge (3,112), motivation (2,832), age (2,668) and incentive (1,558). The conculsion of this research, that dominant variables affecting the performance of the TB officers respectively were knowledge, motivatoin, age and incentives. Key word : Performance TB of officers at Primary Health Centers